2012
DOI: 10.1136/oemed-2011-100529
|View full text |Cite
|
Sign up to set email alerts
|

High urinary bisphenol A concentrations in workers and possible laboratory abnormalities

Abstract: Higher occupational BPA exposure, reflected in urinary concentrations of BPA, may be associated with thyroid hormone disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 26 publications
2
38
1
2
Order By: Relevance
“…Indeed recent studies have shown that workers in epoxy resin factories can have approximately 1000 times higher urinary BPA concentrations compared with control groups (He et al, 2009;Melzer et al, 2010;Wang et al, 2012). The highest levels measured were almost up to 10 mM (Wang et al, 2012), which is within the effective concentration range of Ca 21 channels block by BPA. High exposure to BPA has also been reported for patients, particularly premature infants undergoing intensive medical care treatment (Calafat et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed recent studies have shown that workers in epoxy resin factories can have approximately 1000 times higher urinary BPA concentrations compared with control groups (He et al, 2009;Melzer et al, 2010;Wang et al, 2012). The highest levels measured were almost up to 10 mM (Wang et al, 2012), which is within the effective concentration range of Ca 21 channels block by BPA. High exposure to BPA has also been reported for patients, particularly premature infants undergoing intensive medical care treatment (Calafat et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…BPA was first synthesized in 1891, and as early as in 1936 it was demonstrated that it imitates the activity of the hormone estradiol (Dodds and Lawson 1936). Despite a very strong estrogen activity, BPA has been commercially used since 1957, and despite the fact that its endocrine-disrupting activity was discovered (Krishnan et al 1993), BPA has become a high production volume chemical (Wang et al 2012). Worldwide annual production, which in the case of BPA reached 4.6 million t in 2012, is constantly increasing.…”
Section: Bisphenol Amentioning
confidence: 99%
“…In vitro studies have shown that BPA has the ability to bind to thyroid hormone receptors (35) and human studies have observed associations between higher BPA levels and altered levels of thyroid hormones (36)(37)(38)(39)(40) . Thyroid hormones regulate basal metabolism and the impact of even small alterations to thyroid hormone levels on body composition is evidenced by weight changes in patients with thyroid dysfunction (41)(42)(43) .…”
mentioning
confidence: 99%